2004
DOI: 10.1007/s00436-004-1251-0
|View full text |Cite
|
Sign up to set email alerts
|

Intra-strain clonal phenotypic variation of Tritrichomonas foetus is related to the cytotoxicity exerted by the parasite to cultured cells

Abstract: As observed in most of the investigated trichomonads, a strain of Tritrichomonas foetus includes different parasite subpopulations. Such population diversity might account for important properties such as the ability of the parasite to destroy host cells. The aim of this study was to characterize the cytotoxicity exerted by subpopulations (named as K1, K2, K3, K4 and K5) of an isolate of T. foetus on epithelial cultured cells. The five populations studied here destroyed epithelial monolayers at different rates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…18 Both structural findings might be directly related, because protease-rich vacuoles seem to be forward-directed cytoplasmic expansions associated with cell migration or invasion. 10 Therefore, osteoblasts might respond to CA by performing migration and/or invasion. Thus, it is reasonable to infer that the in vivo use of high amounts of CA might induce bone tissue invasiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Both structural findings might be directly related, because protease-rich vacuoles seem to be forward-directed cytoplasmic expansions associated with cell migration or invasion. 10 Therefore, osteoblasts might respond to CA by performing migration and/or invasion. Thus, it is reasonable to infer that the in vivo use of high amounts of CA might induce bone tissue invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Appropriate controls were performed by using sodium dodecyl sulfate (SDS)-disrupted cells which corresponded to 100% of cell lysis. 10 In addition, spontaneous release of 3 H-thymidine was measured in untreated HOB cells. One hunder microliters of the supernatant of each one of the experimental conditions was poured into vials containing 900 L scintillation liquid (CytoScint; ICN Biochemicals, Costa Mesa, CA).…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%
“…They also showed various degrees of contact – dependent and contact – independent cytotoxicity. Contact – independent cytotoxicity was strictly related to the degree of enzyme activation of an extracellular protease [ 49 ]. Furthermore, it was shown that extracellular proteinases such as CP8 of T. foetus bovine isolate cleaved C3b (the bigger fragment of two C3 component in the original paper designed as C3a) to small fragments, which could play a role in evasion of complement killing in vivo as a result of preventing completion of complement activation cascade [ 50 ].…”
Section: Pathogenesismentioning
confidence: 99%
“…This was probably because there was no inflammatory response in the samples that were positive for the protozoon. The lack of inflammatory response results from the parasite's lack of invasiveness and the fact that it becomes attached to the mucosa of the reproductive tract without triggering any inflammatory response, thereby maintaining the structural integrity of the vaginal mucosal membrane in nonpregnant cows (DA ROCHA-AZEVEDO et al, 2005;SINGH et al, 2004). The presence of UDECs in five of the thirteen samples can be considered to be due to the timing of the estrous cycle and this was unrelated to the presence of T. foetus.…”
Section: Discussionmentioning
confidence: 99%